The Relationship Between Mother's Knowledge About Nutrition Provision With An Improvement Of Stunting Children's Weight - Yuyun Rahayu; Sandriani Sandriani; Nailah Ameliasari; Euis Teti Hayati (Asy-Syifa : Journal of Science and Technology Nursing, 2023)
Purpose: The purpose of the study was to determine the relationship between mothers' knowledge about nutrition and weight gain of stunting children in the Lumbung Public Health Center, Ciamis Regency. Methods: The quantitative research method uses a correlational analytic design with a retrospective approach. The population in this study were all mothers who had to stunt children under five in the Lumbung Health Center working area of as many as 65 research samples. The data collection method used a questionnaire, with chi-square data analysis. Results: The results showed that 33 children experienced weight gain with the criteria of good maternal knowledge, with a statistical test p-value of 0.000 <0.05. Conclusion: There is a Relationship between Mother's Knowledge about Nutrition Giving and Wight Loss for Stunting Children in the Lumbung Health Center Work Area.